2020
DOI: 10.1519/jsc.0000000000002596
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Vented Mouthguard on Physiological Responses in Handball

Abstract: Schulze, A, Laessing, J, Kwast, S, and Busse, M. Influence of a vented mouthguard on physiological responses in handball. J Strength Cond Res XX(X): 000-000, 2018-Mouthguards (MGs) improve sports safety. However, airway obstruction and a resulting decrease in performance are theoretical disadvantages regarding their use. The study aim was to assess possible limitations of a "vented" MG on aerobic performance in handball. The physiological effects were investigated in 14 male professional players in a newly dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…Schulze et al [11] as well as Garner et al [27] reported similar results to the current study. Garner et al [27] suspected a change in jaw position and thus a mechanical-anatomical improvement in airflow dynamics, which may reduce the breathing frequency with * significantly different from co/ # significantly different from MGvent/ + significantly different from nMG/Co = no mouthguard; MGvent = custommade mouthguards with breathing channels; nMG = custom-made mouthguards without breathing channels; mean = group mean values; SD = standard deviation;VO 2 = oxygen uptake/min; VCO 2 = carbon dioxide production/min; RR = respiratory rate; V T = tidal volume; V E = ventilation/ min; Ti = inspiratory time; Te = expiratory time; FetO 2 = end-tidal fractional oxygen concentration; FetCO 2 = end-tidal fractional carbon dioxide concentration; SV = stroke volume; CO = cardiac output; HR = heart rate; avDO 2 = arteriovenous oxygen difference; RQ = respiratory quotient; Lactate = blood lactate, n 2 p = partial eta squared.…”
Section: Ventilatory and Metabolic Parameters Under A Maximal Loadsupporting
confidence: 90%
See 4 more Smart Citations
“…Schulze et al [11] as well as Garner et al [27] reported similar results to the current study. Garner et al [27] suspected a change in jaw position and thus a mechanical-anatomical improvement in airflow dynamics, which may reduce the breathing frequency with * significantly different from co/ # significantly different from MGvent/ + significantly different from nMG/Co = no mouthguard; MGvent = custommade mouthguards with breathing channels; nMG = custom-made mouthguards without breathing channels; mean = group mean values; SD = standard deviation;VO 2 = oxygen uptake/min; VCO 2 = carbon dioxide production/min; RR = respiratory rate; V T = tidal volume; V E = ventilation/ min; Ti = inspiratory time; Te = expiratory time; FetO 2 = end-tidal fractional oxygen concentration; FetCO 2 = end-tidal fractional carbon dioxide concentration; SV = stroke volume; CO = cardiac output; HR = heart rate; avDO 2 = arteriovenous oxygen difference; RQ = respiratory quotient; Lactate = blood lactate, n 2 p = partial eta squared.…”
Section: Ventilatory and Metabolic Parameters Under A Maximal Loadsupporting
confidence: 90%
“…Studies found that this type of MG reduced ventilation (V E ) without negatively affecting performance or oxygen uptake. It was also found that when using these self-adapted MGs with breathing channels, blood lactate was often lower compared to that with the use of a traditional self-adapted MG or no MG [9][10][11][12]. These results suggest improved alveolar V E , which potentially increases respiratory efficiency.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations